2001
DOI: 10.1016/s0926-6410(01)00010-6
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic volume predicts performance on tests of cognitive speed and decreases in healthy aging

Abstract: Recent studies have indicated a role for the thalamus in attention, arousal and the capacity to perform tasks of speeded information processing. The present study evaluated the role of the thalamus in age-related cognitive decline by investigating the correlations between thalamic volume, cognition and age. This was done in 57 healthy subjects ranging from 21 to 82 years of age. All subjects underwent neurocognitive testing with information processing tests and structural magnetic resonance imaging. A signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
88
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 45 publications
17
88
0
2
Order By: Relevance
“…A number of studies have examined some morphometric differences as they relate to performance on cognitive tasks, but little is known about morphometric differences as they relate to individual differences in speed-of-processing measures such as response time (RT). One study used region-of-interest (ROI) methods and reported that increased volume of the thalamus was correlated with faster performance on speeded neuropsychological tests (measured in seconds) in young and middle-aged adults, but not in older subjects (Van der Werf et al, 2001). A similar ROI study found no age-independent relationships between speeded neuropsychological test performance and volumes of the hippocampus, parahippocampus, or total brain volume (Tisserand, Visser, van Boxtel, & Jolles, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have examined some morphometric differences as they relate to performance on cognitive tasks, but little is known about morphometric differences as they relate to individual differences in speed-of-processing measures such as response time (RT). One study used region-of-interest (ROI) methods and reported that increased volume of the thalamus was correlated with faster performance on speeded neuropsychological tests (measured in seconds) in young and middle-aged adults, but not in older subjects (Van der Werf et al, 2001). A similar ROI study found no age-independent relationships between speeded neuropsychological test performance and volumes of the hippocampus, parahippocampus, or total brain volume (Tisserand, Visser, van Boxtel, & Jolles, 2000).…”
mentioning
confidence: 99%
“…Since RT measures generally show age-related slowing and since there are well-known age-related changes in regional brain structures (Tisserand & Jolles, 2003;Van Petten et al, 2004), we examined both middle-aged and senior adults. Only the thalamus, hippocampus, and parahippocampus have been studied in previous research designed to link neuropsychological test speed to ROI morphometry (Tisserand et al, 2000;Van der Werf et al, 2001); however, use of VBM assesses the entire brain. We hypothesized (1) that RT in a memory task would correlate with GM or WM volumes in areas previously associated with memory (Cabeza & Nyberg, 2000;Tisserand & Jolles, 2003;Van Petten et al, 2004) and (2) volume in these areas would not be related to RT in a simple stimulus-response task.…”
mentioning
confidence: 99%
“…12 triggered in response to decline in bottom-up processing (see Grady, 2012, Madden, 2007. By comparison, research aimed at linking age-related changes in cortico-subcortical connectivity and cognitive function has been scarce, though age-related decreases in processing speed have been related to thalamic and prefrontal volume (Van Der Werf et al, 2001). It is possible that the different brain systems that support both stimulus-driven and feature-based memory driven attention capture are impacted by age in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Salthouse, 1996). Decline in the structural integrity of white-matter tracts with ageing (Rabbitt et al 2007;Turken et al, 2008;Van Der Werf et al, 2001) can account for this generalized slowing of brain computations needed for feedback processing and would also explain the ageing-related increase of disengagement costs following capture of the eyes by distracters held in WM(see also Cashdollar et al, 2013). Deficits in disengaging attention with ageing are most likely mediated by impaired frontoparietal networks implicated in selection and executive control, which may fail to suppress distracter-related activity in visual cortex Zanto et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Les modifications neu-roanatomiques sont plus importantes dans les régions frontales (Haug et Eggers, 1991) : réduction générale du volume cérébral de 10 % dans le cortex frontal contre 1 % en temporal, pariétal ou occipital ; réduction de la taille cellulaire après 65 ans qui atteint 43 % dans le cortex préfrontal contre 11 % en pariétal, et 13 % en occipital. La baisse de volume céré-bral concerne aussi le thalamus (Van Der Werf et al, 2001) et le striatum (Gunning-Dixon et al, 1998). L'atrophie cérébrale au cours du vieillissement affecte les circuits fronto-striato-palido-thalamo-frontaux (Alexander et al, 1986) connectant le cortex frontal aux noyaux gris centraux ; ces boucles jouent un rôle important dans la régulation des comportements, des émotions et des fonctions cognitives complexes.…”
Section: Rôle Spécifique Du Vieillissement Dans La Vulnérabilité Suicunclassified